2015
DOI: 10.1063/1.4906776
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nonthermal electrons on plasma expansion into vacuum

Abstract: The expansion of semi-infinite plasma into vacuum is analyzed with a hydrodynamic model for cold ions assuming electrons modelled by a kappa-type distribution. Similarly to Mora study of a plasma expansion into vacuum [P. Mora, Phys. Rev. Lett. 90, 185002 (2003)], we formulated empirical expressions for the electric field strength, velocity, and position of the ion front in one-dimensional nonrelativistic, collisionless isothermally expanding plasma. Analytic expressions for the maximum ion energy and the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…At the moving boundaries where quasi-neutrality down, inclusion of Poisson's equation around the discontinuities may lead to localized short wavelength oscillations (Gurevich & Pitaevsky 1975). Additionally, we note that a variety of instabilities may arise with the introduction of multiple ion species (Gurevich, Par & Pitaevski 1973;Elkamash & Kourakis 2016), non-Maxwellian electron distributions (True 1981;Bennaceur-Doumaz et al 2015) and magnetic fields (Gurevich & Pitaevsky 1975;García-Rubio et al 2016). All of these auxiliary effects are beyond the scope of the present study.…”
Section: Appendix a Review Of Self-similar Formulationmentioning
confidence: 83%
See 1 more Smart Citation
“…At the moving boundaries where quasi-neutrality down, inclusion of Poisson's equation around the discontinuities may lead to localized short wavelength oscillations (Gurevich & Pitaevsky 1975). Additionally, we note that a variety of instabilities may arise with the introduction of multiple ion species (Gurevich, Par & Pitaevski 1973;Elkamash & Kourakis 2016), non-Maxwellian electron distributions (True 1981;Bennaceur-Doumaz et al 2015) and magnetic fields (Gurevich & Pitaevsky 1975;García-Rubio et al 2016). All of these auxiliary effects are beyond the scope of the present study.…”
Section: Appendix a Review Of Self-similar Formulationmentioning
confidence: 83%
“…Semi-analytic models with a more accurate portrayal of the ion front boundary layer (Mora 2003;Medvedev 2011) have shown that the self-similar domain of validity can be extended earlier in time and further in space. Many variations of this problem, beyond the scope of the present discussion, include non-isothermal expansion (Mora & Pellat 1979;Grismayer et al 2008), non-Maxwellian initial distributions (Gurevich & Meshcherkin 1981a;True 1981;Akbari-Moghanjoughi 2015;Bennaceur-Doumaz et al 2015), magnetic fields (García-Rubio, Ruocco & Sanz 2016) and multiple ion species (Elkamash & Kourakis 2016). Some attention has been given to the case of a finite plasma (Medvedev 2005;Murakami & Basko 2006), but still with infinite boundary conditions in the vacuum.…”
mentioning
confidence: 98%
“…The distribution of those electrons accelerated at the vacuum-plasma interface is of importance for ion acceleration processes at the rear side of a target with finite width, and it is of interest for the models describing ion acceleration. [70][71][72][73][74][75][76][77][78][79][80][81][82][83] The evolution shown in Fig. 12, illustrating how the most energetic electron penetrate into the dense plasma, are therefore of particular relevance for relatively thin target foils for which the cutoff in the electron momentum remains 'preserved' till the arrival of the fastest electrons at the rear face.…”
Section: Discussionmentioning
confidence: 99%
“…At this point, we need to adopt an explicit form of the distribution function. There are several reasonable options, such as the κ or Vasyliunas distribution function [39][40][41][42], the Tsallis distribution function [43][44][45], a super-Gaussian [46,47], a Maxwellian with a supra-thermal component [48] or a Jüttner distribution with a superimposed shift in the momentum [49]. Here, we choose a Cairns-like distribution function.…”
Section: Non-equilibrium Relativistic Distribution Functionmentioning
confidence: 99%